Technical Intelligence and Security Management within the Nigerian Territorial Waters: The Nigerian Navy Challenge - Ngboawaji Daniel Nte; Brebina Kelvin Enoke; Ilyasu Abubakar (Universitas Negeri Semarang, 2022)
With the world becoming a more volatile place and certainly high - threat environments becoming too far and dangerous to send personnel, the insufficiency of human intelligence has placed a greater stress on technical aids in gathering intelligence. Technology has allowed the acquisition of intelligence to rely less on human intelligence. The progeny of modern day equipment - both offensive and defensive has made provision for myriad levels in intelligence gathering. The Gulf of Guinea Basin countries rely heavily on their maritime sector for greater per cent of their exports and imports. The Gulf of Guinea is strategic to the development of West African countries and has been characterized by various maritime crimes, thus the need for technical intelligence and surveillance measures by basin countries to enhance the security of the region. Nigeria is a strategic stakeholder in the maritime security around the Gulf of Guinea with her Navy and Nigerian Maritime Administration and Safety Agency as the lead agencies responsible for her maritime security and safety. This work discusses the various leverage and the challenges of modern surveillance equipment to aid the achievement of securing the Nigerian maritime environment by the Nigerian Navy as well as her involvement in several internal security operations in Nigeria.